STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II B SEKOLAH DASAR SWASTA ISLAM TERPADU AL FURQON TEBAS TAHUN PELAJARAN 2023-2024 - Desi Sopiana; Hifza Hifza; Parni Parni (CV. ADIBA AISHA AMIRA, 2024)
This research is to reveal about: 1). Strategies Used by Teachers to Improve Students' Reading Ability in Class II B 2). Teacher Strategy Steps Used in Improving Students' Reading Ability in Class II B 3). Supporting and Inhibiting Factors for Teacher Strategies in Improving Students' Reading Ability in Class II B. This research uses a qualitative approach with a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the research show that, 1) The strategies used by teachers to improve students' reading skills in class II B of the Al Furqon Tebas Integrated Islamic Private Elementary School for the 2023-2024 academic year are two main strategies that utilize learning media. First, the use of letter card media, Second, the use of picture card media involving pictures, animated videos, and educational applications to introduce the letters of the alphabet, 2) Teacher strategy steps used to improve students' reading skills in class II B elementary schools Al Furqon Tebas Integrated Islamic Private School for the 2023-2024 Academic Year, namely, interactive learning strategies and various media are used to increase students' understanding and interest. These methods, including dividing students into groups, using letter and picture cards, and teacher-led games, successfully create a dynamic and enjoyable learning environment. 3) Supporting and inhibiting factors for teacher strategies in improving students' reading skills in class II B of the Al Furqon Tebas Integrated Islamic Private Elementary School for the 2023-2024 academic year, namely, the existence of modern facilities, teacher enthusiasm and professionalism, as well as interactive learning approaches such as the use of picture cards, has shown positive results in increasing student interest and participation. Despite challenges such as diverse student backgrounds, inefficient learning time, and lack of motivation from families, collaborative efforts between teachers, students, and school management, as well as adjustments to learning strategies, play an important role in creating an effective and inclusive learning environment.